2010
DOI: 10.1186/1749-8546-5-39
|View full text |Cite
|
Sign up to set email alerts
|

Osteoprotective effects of Fructus Ligustri Lucidi aqueous extract in aged ovariectomized rats

Abstract: BackgroundFructus Ligustri Lucidi (FLL) is a commonly used herb for treating bone disorders in Chinese medicine. The present study investigates the anti-osteoporotic activity of FLL aqueous extract in the model of postmenopausal bone loss in aged ovariectomized (OVX) female rats.MethodsAfter eight weeks of treatment of FLL or water, the lumbar spine was scanned by peripheral quantitative computed tomography (pQCT). Effects of FLL water extract on osteogenic and adipogenic differentiations in rat mesenchymal st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 22 publications
2
18
0
Order By: Relevance
“…It was reported that Epimedii Herba‐derived flavonoids could exert anabolic effects on osteoporotic bone from ovariectomized rats by concomitantly promoting osteogenic and suppressing adipogenic differentiation of bone mesenchymal stem cells (MSCs) . This result was similar to our previous finding on the osteoprotective effects of Ligustri Lucidi Fructus aqueous extract in aged ovariectomized rats . Besides, Fructus Psoraleae extract was reported to be effective in increasing the bone density and improving the bone architecture in vivo .…”
Section: Introductionsupporting
confidence: 87%
“…It was reported that Epimedii Herba‐derived flavonoids could exert anabolic effects on osteoporotic bone from ovariectomized rats by concomitantly promoting osteogenic and suppressing adipogenic differentiation of bone mesenchymal stem cells (MSCs) . This result was similar to our previous finding on the osteoprotective effects of Ligustri Lucidi Fructus aqueous extract in aged ovariectomized rats . Besides, Fructus Psoraleae extract was reported to be effective in increasing the bone density and improving the bone architecture in vivo .…”
Section: Introductionsupporting
confidence: 87%
“…We and others demonstrate that FLL improves Bone mineral density (BMD) and bone microstructure as well as bone mechanical strength in both aged (Ko et al, 2010) and growing female rats (Feng et al, 2014) as well as ovariectomized (OVX) rats (Zhang et al, 2006; Lyu et al, 2014; Guo et al, 2016a). FLL exhibited bone protective effects by improving calcium absorption and balance via increasing gene expression of transient receptor potential vanilloid 6 and calcium-binding protein-9k, and by decreasing renal calcium-sensing receptor gene expression (Zhang Y. et al, 2014; Zhang et al, 2015) via stimulating 1.25(OH) 2 D 3 /vitamin D receptor signaling (Feng et al, 2014) through inducing the activity of renal 25-hydroxyvitamin D-1α hydroxylase (Dong et al, 2010), as well as by stimulating parathyroid hormone production in mature normal female rats (Dong et al, 2012) and in type 1 diabetic mice (Zhang Y. et al, 2014).…”
Section: Introductionmentioning
confidence: 91%
“…[14] FLL was shown to stimulate osteogenesis, inhibition of adipogenesis and osteoclastogenesis in rat mesenchymal stem cells in aged OVX rats. [15] FP exhibited osteoblastic proliferation stimulating activity in rat osteoblast-like cell line UMR106 [16] and promoted bone calcification. [17] Recently, a herbal formula named ELP consisting these thee herbs, HP, FLL and FP, in the ratio of 5 : 4 : 1, respectively, has been demonstrated to reduce bone loss at the femoral neck in rats which osteoporosis were caused by ovariectomy and calcium deficiency as well as physical inactivity.…”
Section: Introductionmentioning
confidence: 94%
“…Extracts of HEP and its constituents could inhibit bone resorption, stimulate bone formation and accordingly prevent osteoporosis without hyperplastic effect on uterus in OVX rats . FLL was shown to stimulate osteogenesis, inhibition of adipogenesis and osteoclastogenesis in rat mesenchymal stem cells in aged OVX rats . FP exhibited osteoblastic proliferation stimulating activity in rat osteoblast‐like cell line UMR106 and promoted bone calcification .…”
Section: Introductionmentioning
confidence: 99%